Optimisation of a process for production of pomegranate pulp and flaxseed powder fortified probiotic Greek dahi. (6th February 2018) - Reeta,; Kumar, Sudhir; Rasane, Prasad; Nimmanapalli, Ramadevi
Abstract : Fortified probiotic Greek dahi was formulated with pomegranate pulp (PP) and flaxseed powder (FP). The product variables, viz. PP, FP and incubation time, were optimised based on chemical, sensory and textural attributes. The study revealed that PP significantly affected the acidity and antioxidant content, while FP influenced the sensory and textural properties of the product. The optimum conditions were 15% PP, 2% FP and 12‐h incubation time. The developed fortified probiotic Greek dahi is a potential synbiotic food.